Targeting the DNA methylation–H3K27me3 switch reverses castration resistance and immunosuppression via ADAMTS1-driven collagenolysis - Xiang Wu; Xiaoyi Song; Bo Li; Yuchun Yang; Kunyu Li; Jun Zhu; Yawei Li; Xinming Yang; Yingbo Dai; Zhuangzhuang Zhang (Proceedings of the National Academy of Sciences, 2026)
Castration-resistant prostate cancer (CRPC) lethality arises from epigenetic-driven resistance to androgen deprivation therapy (ADT). Here, we uncover a compensatory epigenetic switch between DNA methylation and H3K27me3-mediated repression as a critical barrier to epigenetic therapy in CRPC. Integrative multiomics analyses reveal that DNMT inhibitors (DNMTis) trigger EZH2-dependent H3K27me3 accumulation at the ADAMTS1 locus—a master collagenase essential for extracellular matrix (ECM) remodeling—perpetuating fibrotic niche formation and therapy resistance. Dual targeting of DNMTs and EZH2 disrupts this epigenetic plasticity, synergistically reactivating ADAMTS1 to degrade collagen-rich stroma, suppress FAK/MAPK mechanotransduction signaling, and reverse epithelial–mesenchymal transition (EMT). Crucially, in immunocompetent models, this strategy achieves >90% tumor suppression and reverses immunosuppression by enhancing cytotoxic CD8 + T cell infiltration 11.4-fold while depleting immunosuppressive macrophages and Tregs. Mechanistically, dual therapy inactivates the FAK/MAPK/EMT axis via ADAMTS1-mediated ECM degradation, overcoming stromal-mediated resistance. Our work establishes epigenetic-ECM coevolution as a hallmark of CRPC and provides a rationally designed combination therapy to dismantle the therapy-resistant niche.